The Need Analysis of Module Development Based on Search, Solve, Create, and Share to Increase Generic Science Skills in Chemistry - Nastiti, D.; Rahardjo, S. B.; VH, Elfi Susanti; Perdana, R. (Jurnal Pendidikan IPA Indonesia, 2018)
Science generic skill is very important for students to solve every problem in learning processes and daily life. The purpose of this research was to explore the students’ needs of the chemistry module based on search, solve, create, and share (SSCS) to increase science generic skills. This research employed a descriptive qualitative method. There were 61 students in XI Grade from two Senior High Schools at Surakarta. The data were collected using questionnaires sheets, interviews, and materials analysis. The research revealed that the module and teaching materials used in the schools have not empowered the science generic skills maximally; also, the teachers remained to adopt discourse method which resulted in a teacher-centered learning. Such learning made the learning activities seemed monotonous, uninteresting, and less motivated the students in building concepts. Thus, the students required alternative teaching materials to increase their science generic skills. In sum, it is necessary to develop a chemistry module on the atomic structure which oriented to the SSCS.